Prospek Pendirian Baitul Maal Wat Tamwil (Bmt) Di Kecamatan Cina Kabupaten Bone - ASMIN, ASRIYUNI (Benefits : Jurnal Ekonomi dan Pariwisata Internasional, 2025)
The existence of BMT as a sharia microfinance institution has an important role for the community, especially small community business actors, in efforts to empower the economy. So researchers are interested in examining the prospects for establishing Baitul Maal Wat Tamwil (BMT) by looking at the various potentials in China District and the level of community need, especially for small businesses, for business capital financing. The aim of establishing BMT in Cina District is to empower the people's economy, eradicate poverty, social poverty can be reduced so that economic justice, prosperity and welfare of the community can be achieved and what is more important is the importance of poverty free from the bondage of loan sharks. This problem is seen using a qualitative approach using descriptive data, namely research in which data is extracted through observation and interviews with informants based on criteria determined by researchers which are considered to support the prospects for establishing BMT in Cina District. The final conclusion is that there are quite good prospects for building BMT in the Cina District in the future because there is potential that supports the establishment of BMT (Strengths and Opportunities) but there are also obstacles (weaknesses and threats) in establishing BMT in the Cina District. So the author created the SO strategy (using strengths to take advantage of opportunities), the WO strategy (minimizing weaknesses to take advantage of opportunities), the ST strategy (using strengths to overcome threats) and the WT strategy (minimizing weaknesses and avoiding weaknesses).